A Review of Perennial Ryegrass Endophytes and Their Potential Use in the Management of African Black Beetle in Perennial Grazing Systems in Australia - Karpyn Esqueda, Mijail; Yen, Alan L.; Rochfort, Simone; Guthridge, Kathryn M.; Powell, Kevin S.; Edwards, Jacqueline; Spangenberg, German C. (Frontiers in Plant Science, 2017)
The major insect pest of Australian cool temperate pastures is the root-feeding insect Heteronychus arator (African black beetle, ABB). Significant pasture damage can occur even at low ABB densities (11 individuals per square metre), and often re-sowing of the whole paddock is required. Mitigation of the effects of pasture pests, and in particular subterranean species such as the larval form of ABB, can be challenging. Early detection is limited by the ability to visualise above-ground symptoms, and chemical control of insects in soil is often ineffective. This review takes a look at the historical events that moulded the pastoral landscape in Australia. The importation route, changes in land management and pasture composition by European settlers may have aided the establishment of ABB in Australia. Perennial ryegrass Lolium perenne is discussed as it is one of the most important perennial agricultural grasses and is widely-sown in moderate-to-high-rainfall temperate zones of the world. Endophytic fungi from the genus Epichloë form symbiotic relationships with cool season grasses such as Lolium perenne (perennial ryegrass). They have been studied extensively and are well documented for enhancing persistence in pasture via a suite of bioactive secondary metabolites produced by the fungal symbionts. Several well-characterised secondary metabolites are discussed. Some can have negative effects on cattle (e.g. ergovaline and lolitrems) while others have been shown to benefit the host plant through deterrence of insect pests from feeding and by insecticidal activity (e.g. peramine, lolines, ergopeptines). Various control methods for ABB are also discussed, with a focus on the potential role of asexual Epichloë endophytes.